Mercury contents of selected marine manganese nodules - Robert C Harriss (PANGAEA, 2023)
Manganese nodules were selected from various areas of the Pacific, Indian and Atlantic ocean. They were analysed using a mercury vapour discharge technique. The minimum precision of the technique as determined by multiple analyses of individual samples was +- 12 per cent of the amount present.